Original paperArachidonic acid metabolism in TNF, CD178 (CD95 ligand) and ceramide-mediated cytotoxicity - Ołdak, Monika; Joźwiak, Jarosław; Maksym, Radosław; Malejczyk, Jacek (Archives of Medical Science, 2007)
Introduction: Arachidonic acid release has been reported to play a significant role in TNF-induced cytotoxicity. However, the role of this signalling cascade in CD178-(CD95 ligand)mediated cytotoxicity remains unclear. The aim of the study was to investigate the role of arachidonic acid metabolism in TNF- and CD95-mediated cytotoxicity. Material and methods: Naturally TNF-sensitive A9 and CD178-sensitive A9-CD95 (the cells stably transfected with human CD95) cell lines were subjected to inhibitors of phospholipase A2 (AACOCF3, PACOCF3), lipoxygenase (NDGA) and cycloxygenase (indomethacin). Results: We showed that the cytotoxic activity of TNF could by inhibited by AACOCF3 and PACOCF3, inhibitors of phospholipase A2 as well as by NDGA, displaying anti-lipoxygenase and anti-oxidant inhibitory activity. In contrast, none of the tested inhibitors of arachidonic acid metabolism affected CD178-mediated cytotoxicity in A9-CD95 cells stably expressing CD95. Cytotoxicity mediated by C6-ceramide, a possible mediator of TNF- and CD178-mediated cytotoxicity, was also unaffected by these inhibitors. Conclusions: The above facts strongly suggest that CD95- as well as C6 ceramide-induced cell death does not depend on arachidonic acid metabolism.